Environmental perfluorooctane sulfonate exposure drives T cell activation in bottlenose dolphins. Issue 9 (19th April 2017) - Soloff, Adam C.; Wolf, Bethany Jacobs; White, Natasha D.; Muir, Derek; Courtney, Sean; Hardiman, Gary; Bossart, Gregory D.; Fair, Patricia A.
Abstract: Perfluoroalkyl acids (PFAAs) are highly stable compounds that have been associated with immunotoxicity in epidemiologic studies and experimental rodent models. Lengthy half‐lives and resistance to environmental degradation result in bioaccumulation of PFAAs in humans and wildlife. Perfluorooctane sulfonate (PFOS), the most prevalent PFAA detected within the environment, is found at high levels in occupationally exposed humans. We have monitored the environmental exposure of dolphins in the Charleston, SC region for over 10 years and levels of PFAAs, and PFOS in particular, were significantly elevated. As dolphins may serve as large mammal sentinels to identify the impact of environmental chemical exposure on human disease, we sought to assess the effect of environmental PFAAs on the cellular immune system in highly exposed dolphins. Herein, we utilized a novel flow cytometry‐based assay to examine T cell‐specific responses to environmental PFAA exposure ex vivo and to exogenous PFOS exposure in vitro . Baseline PFOS concentrations were associated with significantly increased CD4 + and CD8 + T cell proliferation from a heterogeneous resident dolphin population. Further analysis demonstrated that in vitro exposure to environmentally relevant levels of PFOS promoted proinflammatory cytokine production and proliferation in a dose‐dependent manner. Collectively, these findings indicate that PFOS is capable of inducing proinflammatory interferon‐gamma, but not immunoregulatory interleukin‐4 production in T cells, which may establish a state of chronic immune activation known to be associated with susceptibility to disease. These findings suggest that PFOS directly dysregulates the dolphin cellular immune system and has implications for health hazards. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : Flow cytometry‐based assay examined T cell‐specific responses to environmental perfluoroalkyl acid exposure ex vivo and exogenous perfluorooctane sulfonate (PFOS) in vitro . PFOS concentrations in dolphins were associated with significantly increased CD4 + and CD8 + T cell proliferation. In vitro PFOS exposure promoted proinflammatory cytokine production and proliferation. PFOS induced proinflammatory interferon‐gamma, but not immunoregulatory interleukin‐4 production in T cells suggestive of chronic immune activation. PFOS directly dysregulates the dolphin cellular immune system and has implications for health.